If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17x + -25 = 19 + -15x Reorder the terms: -25 + -17x = 19 + -15x Solving -25 + -17x = 19 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. -25 + -17x + 15x = 19 + -15x + 15x Combine like terms: -17x + 15x = -2x -25 + -2x = 19 + -15x + 15x Combine like terms: -15x + 15x = 0 -25 + -2x = 19 + 0 -25 + -2x = 19 Add '25' to each side of the equation. -25 + 25 + -2x = 19 + 25 Combine like terms: -25 + 25 = 0 0 + -2x = 19 + 25 -2x = 19 + 25 Combine like terms: 19 + 25 = 44 -2x = 44 Divide each side by '-2'. x = -22 Simplifying x = -22
| 14x+x+x+4+(-6)=14x+x+x+4-6 | | 0=9x+81 | | 7+4x-1=12 | | 3(2x-1)-6x=-4 | | 8(n-2)-3(n-4)=6(n-7)+8 | | 3x-7=3x+13 | | -6(4x-2)=-24x+12 | | 1/4(4q+12)=2+18-3q | | 0.25+4.75=6 | | -12+21=-3 | | 18x+9y=360 | | 4x-11=-23 | | 3(2x-4)=21 | | 2x-4+0.5(2+8x)=0 | | 36-11=5(x-4) | | 33+3y-12=12y-9-4y | | -1y-22-1y=-16 | | 15=-3(n-4) | | x^2+26x+112=0 | | x+20+4x=-33-4x-37 | | 6x-6=10x+15-15 | | 5-(3)= | | 48f+6.4=-8.48 | | 10y+9=-3 | | 2(-2x+4)=8 | | -4(2x-3)-3-8x=-11 | | 24-6k=6[4-k] | | 10+45u= | | a+140=a+0.05a | | 15-6x+7-3x= | | -16+6=-6r+2 | | 10x-3y=24 |